Effects of seasonal variations and pond age on trace elements and their correlations with plankton productivity in commercial freshwater crayfish (cherax cainii austin, 2002) earthen ponds - Tulsankar, Smita; Cole, Anthony John; Gagnon, Marthe Monique; Fotedar, Ravi (WILEY, 2020)
Seasonal variations can affect the concentration of trace elements, and the change in their concentrations can affect the natural productivity of freshwater aquaculture ponds. Hence, we studied the seasonal variations of the 12 pre-selected trace elements (Co, Cu, Fe, Mn, Zn, Se, Ca, Mg, P, S, Al, Si) and their relationships with primary and secondary productivity in two aged ponds, stocked with three different life stages of marron (Cherax cainii), for a period of 1 year. Trace element analysis was performed by using (Agilent, ICP-OES). Except Co and Se, all trace elements, and primary and secondary productivity were influenced by seasonal variation. The pond age significantly influenced the concentrations of some trace elements. On a seasonal basis, trace elements were positively correlated with the plankton abundance, species diversity, and wet and dry plankton weights. Seasonal variations and pond age affected the dissolved concentrations of trace elements and plankton productivity.